Exchanges between Two Rivers: Possibilities for Teaching Writing in the Northwest Territories - Catlin, Susan Jane (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
My action research investigation into place-conscious writing practices invited experienced Non-Aboriginal teachers from the Northwest Territories to think through writing practices that might engage Northern students, many of whom are Indigenous. In this paper, I will focus on what the teachers had to say about the influences of aspects of Indigenous oral traditions on their writing pedagogies. I will consider the possibility that multiliteracies might provide a more dynamic conception of literacy that invites student engagement through multimodal connections and opens up spaces for Indigenous ways of knowing and being in approaches to teaching writing. Key words: writing pedagogy, multiliteracies, Indigenous education, oral traditions